Utilization of Claude Artificial Intelligence Technology to Increase the Effectiveness of Conveying Opinions about Bullying - Chatrin Simarmata; Lilis Karolina Perangin-angin; Maikel Brekana Ginting; Windi Aura; Trisnawati Hutagalung; Nurul Azizah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The use of artificial intelligence (AI) in the Claudia version is believed to be able to assist students who have difficulty writing coherent and objective opinions. This study aims to determine the effectiveness of using the Claude version of the AI to improve the effectiveness of opinion writing on bullying for grade 1 students. This study took place in the odd semester of the 2025/2026 academic year at SMA Negeri 4 Pematang Siantar. The Claude version of the AI was used as a companion tool in the opinion-writing process. The respondents of this study were a group of class X students. Data were collected through objectively designed observation and interview guidelines. Data on students' opinion writing on bullying before and after using the AI were analyzed descriptively and qualitatively. The results showed that the use of the Claude version of the AI improved the clarity of ideas, writing structure, and word choice when students expressed their opinions. Students felt more supported because the AI provided examples, suggestions, and corrections that made it easier for them to express their opinions regarding bullying. Furthermore, students became more confident and motivated when expressing their opinions. The use of the Claude version of the AI has proven effective as a tool in improving students' ability to express their opinions on bullying issues.